2021
DOI: 10.1016/j.envres.2021.112246
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Assessment of COVID-19 pandemic effects on ship pollutant emissions in major international seaports

Abstract: This study aims to investigate the coronavirus disease (COVID-19) pandemic effects and associated restrictive rules on ship activities and pollutant emissions (CO 2 , SO X , NO X , PM, CO, CH 4 ) in four major seaports, namely the Ports of Singapore, Long Beach, Los Angeles, and Hamburg. We used 2019 as the baseline year to show the business-as-usual emission and compared with the estimated quantity during the July 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…However, the study results by Liu et al (2021) showed that the ship emissions in ports increased by an average of 79 % because of the prolonged turnaround time in port. It is important that most ship emissions occurred during the extended staying time at berth and anchorage areas due to longer operational times caused by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study results by Liu et al (2021) showed that the ship emissions in ports increased by an average of 79 % because of the prolonged turnaround time in port. It is important that most ship emissions occurred during the extended staying time at berth and anchorage areas due to longer operational times caused by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Port cities are characterized by the developed maritime trade, densely populated, and higher industrial levels. However, few researchers analyze the impacts of the epidemic on ports ( Fuwape et al, 2021 ; Liu et al, 2021 ). Ito et al (2020) analyzed the cruise industry during the context of the pandemic, and they focused on the impact of confirmed cases of COVID-19 on the changes in cruise passengers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for the reasons we use panel data, they are as follows. Firstly, panel data have a higher freedom degree compared with the time series or cross-section data ( Liu et al, 2021 ); Secondly, the panel regression model can become a variable coefficient regression model to study the effects of different elements with different port cities. Thirdly, kinds of variables can be added to ignore the effects of unobserved factors.…”
Section: Model Specification and Descriptionmentioning
confidence: 99%
See 1 more Smart Citation